A 22% Efficient Semiconductor/Liquid Junction Solar Cell—the Photoelectrochemical Behavior of n-WSe2 Electrodes in the Presence of I2/I- in Aqueous Electrolyte. (1988) - Campet, G.; Azaiez, C.; Levy, F.; Bourezc, H.; Claverie, J.
Abstract : One of the most efficient semiconductor/liquid-junction photoelectrochemical cells (PEC) reported to date is presented. It consists of a SeCl4 -grown n-WSe2 single crystal anode, with a 3.10 16 cm -3 conduction-band electronic density, and a platinum cathode. Both electrodes are immersed in a 2M KI + 0.005M I2 aqueous electrolyte. The calculations of the main physical parameters determining the high value (22%) of the visible light-to-electrical energy conversion efficiency have been carried out. We particularly show that the lifetime of the photogenerated holes is larger than their transit time across the space-charge so that the carriers reach the semiconductor surface, where they can react with the electrolyte, without recombining.